The use of inertial measurement units for analyzing change of direction movement in sports: A scoping review - Alanen, A. M.; Räisänen, A.; Benson, L.; Pasanen, K. (International Journal of Sports Science & Coaching, 2021)
Change of direction movement is common in sports and the ability to perform this complex movement efficiently is related to athlete's performance. Wearable devices have been used to evaluate aspects of change of direction movement, but so far there are no clear recommendations on specific metrics to be used.